Implementing the Cooperative Learning type Scramble Method to Enhance Arabic Sentence Writing Skills - Ardiansyah, Muhammad; Sholihah, Faizatun; Marlina, Leny (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study is a solution to the problem of low Arabic sentence writing skills in class V MI Hamzanwadi East Lombok. Among the factors causing this is the lack of writing practice, and teachers also often face obstacles in teaching writing Arabic sentences that are effective and interesting for students. The purpose of the study was to evaluate in detail the improvement and implementation of the scramble method in improving Arabic sentence writing skills of the material "ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø©". The research method used is Kurt Lewin's PTK model structured in two cycles, including: planning, action, observation, and reflection. Data collection techniques used interviews, observations and tests. The results revealed a significant increase in teacher activity (from 70 in cycle I to 83.6 in cycle II) and student activity (from 72 to 85). Writing skills with the scramble method also showed improvement, with the class average score increasing from 65.69 in cycle I to 83 in cycle II. The learning completeness rate increased dramatically from 46.15% in cycle I to 84.61% in cycle II. This study highlights the importance of scramble method in improving Arabic language learning in MI. Its practical implications include recommendations for the application of this method in Arabic language teaching in MI as well as directions for further research in this field, strengthening the educational foundation at this level.